2011
DOI: 10.1002/msc.205
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Foot Health Education for Patients with Rheumatoid Arthritis: A Narrative Review

Abstract: The effect of PE delivered from a podiatric context needs to be explored, and the nature and requirements of PE for individuals with RA-related foot problems from a patient and practitioner perspective requires investigation. Alternative and innovative ways of providing PE and, potentially, self-management need to be investigated and defined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
17
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 51 publications
4
17
0
1
Order By: Relevance
“…Podiatrists perceive it as a valued and beneficial activity supporting aspects of foot management that patients can perform themselves [11]. Despite recommendations for an increased role of the patient in foot health [4-6], little is known from the patient perspective.…”
Section: Introductionmentioning
confidence: 99%
“…Podiatrists perceive it as a valued and beneficial activity supporting aspects of foot management that patients can perform themselves [11]. Despite recommendations for an increased role of the patient in foot health [4-6], little is known from the patient perspective.…”
Section: Introductionmentioning
confidence: 99%
“…The previous studies on RA suggested that lack of information about RA was a critical factor for the treatment delay (23,24). Hence, RA patients need to be well-informed and educated on modern treatment, which is a core component of care (4); therapeutic patient education is one of the essential components of the health system (25). A qualitative study in eight European countries on six rheumatic conditions suggested that there is a need for disease-specific interventions through non-physician health professionals in case of musculoskeletal care (26).…”
Section: Discussionmentioning
confidence: 99%
“…There is currently a limited amount of research that describes the results of overall foot educational interventions in these patients [10]. Due to this need, we have proposed carrying out sessions of podiatric therapeutic education in patients with RA.…”
Section: Introductionmentioning
confidence: 99%
“…To carry out this educational intervention, and to be able to value its effectiveness, it was necessary to elaborate and validate a questionnaire that covered these aspects. Due to the limited literature on the subject [10], there is currently no validated questionnaire. For this reason, the main aim of this work was to validate a questionnaire, through the Delphi method, to increase our knowledge of different aspects of overall foot health in patients with RA.…”
Section: Introductionmentioning
confidence: 99%